El isópodo Neracilia californica, simbionte de Cytarichthys gilberti (Bothidae) en el sistema lagunar de Huizache-Caimanero, Sinaloa, México - Alvarez León, Ricardo (1981)
A specimen of the isopod Nerocilia californica is reported as a symbiont of a juvenile flatfish (Cytarichthys gilberti) from Sinaloa, Mexico. (Agua Dulce weir, Huizache-Caimanero lagoon system), captured during collection of postlarvae and juvenile penaeid shrimp.